Evaluation of selected quality characters in the collection of naked oats in Czech conditions - Nedomova, Lenka; Milotova, Jarmila (MTT, 2004)
Based on increasing use of oats for human nutrition and newly developed processing methods, there is a need of more detailed defining its grain quality. Varieties with growing characteristics suitable for the given environment and grain quality acceptable for defined end use are assumed to meet requirements of both growers and the processing industry. In 2000-2003, 42 hulless varieties from the oat collection were grown in the field in plots of 2.5 m2 without replications and evaluated for growing characteristics. After harvest with a combine-harvester, basic parameters of the grain (yield estimation, 1000-grain weight, volume weight, screening fractions, percentage of hulled grains) were evaluated and nutritional characteristics (content of nitrogen, starch, fat and fibre) were determined using the NIR technique. Results confirmed a high variation in all characters examined. The highest difference between maximum and minimum values in absolute values was found in starch (12.1), however due to high starch content the variation coefficient was lowest (4.5 %). The highest variation coefficient was calculated for fibre content (53 %). This value was markedly affected by a generally low fibre content and relatively high occurrence of hulled grains in some materials depending on weather conditions of the year. The nitrogen (respectively starch, fat, and fibre) content in the examined materials varied from 15.7 to 24.7 (from 52.3 to 64.4, from 2.9 to 8.2, and from 0.2 to 3.8, respectively), the maximum difference between years was 2.1 (2.6, 1.1, and 1.0, respectively). Correlation coefficients were calculated. Supported by the Ministry of Agriculture of the Czech Republic, National Agency for Agricultural Research, Project No. QD 0057.
Keywords: Ka; genetic resources; quality; naked oats